2007
DOI: 10.1002/pd.1890
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of maternal serum PAPP‐A in the first trimester and the risk of pre‐eclampsia

Abstract: Background Low levels of pregnancy associated plasma protein-A (PAPP-A) have been previously shown to be associated with pregnancies that subsequently develop pre-eclampsia. The objective of this study was to establish the relative risk for pre-eclampsia at various PAPP-A levels as an aid to counselling and follow up of pregnancies.Methods Maternal serum PAPP-A and free ß-human chorionic gonadotropin (ß-hCG) levels at 11 to 13 weeks of gestation from 224 singleton pregnancies that subsequently developed pre-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
114
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 31 publications
7
114
1
4
Order By: Relevance
“…Using single biochemical markers usually has a low predictive value in the first trimester. PAPP-A, a glycoprotein synthesized in the placenta, has been shown to be a powerful predictive biochemical marker of PE when combined with Doppler ultrasound, reaching 70% sensitivity at 95% specificity (Spencer et al, 2008;Goetzinger et al, 2010;Anderson et al, 2011). However, some recent studies evaluating PAPP-A as a firsttrimester predictive marker for PE showed conflicting results that indicated no differentiation between complicated and uncomplicated pregnancies (Mikat et al, 2011;Stirnemann et al, 2011).…”
mentioning
confidence: 94%
“…Using single biochemical markers usually has a low predictive value in the first trimester. PAPP-A, a glycoprotein synthesized in the placenta, has been shown to be a powerful predictive biochemical marker of PE when combined with Doppler ultrasound, reaching 70% sensitivity at 95% specificity (Spencer et al, 2008;Goetzinger et al, 2010;Anderson et al, 2011). However, some recent studies evaluating PAPP-A as a firsttrimester predictive marker for PE showed conflicting results that indicated no differentiation between complicated and uncomplicated pregnancies (Mikat et al, 2011;Stirnemann et al, 2011).…”
mentioning
confidence: 94%
“…For example, unusually low levels of PAPPA in the first trimester may be indicative of increased risk of fetal genetic disorders such as Down's syndrome (Brambati et al 1993) and Cornelia de Lange syndrome (Aitken et al 1999). Furthermore, low circulating PAPPA levels are also associated with higher risk of low birth weight, IUGR, and preeclampsia , Kwik & Morris 2003, Dugoff et al 2004, Spencer et al 2008, which are characterized by impaired trophoblast invasion. Although PAPPA is highly expressed in human placenta (Tornehave et al 1984), this is not the case in the mouse (Qin et al 2002, Soe et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Various serum proteins are considered to contribute to the symptoms of PE, such as placental growth factor (PlGF), vascular endothelial growth factor (VEGF), soluble vascular endothelial growth factor receptor-1 (sVEGFR-1), soluble fms-like tyrosine kinase-1(sFlt-1), placental protein 13 (PP-13), pregnancy-associated plasma protein A (PAPP-A), human chorionic gonadotrophin (HCG), soluble endoglin (sEng), alpha fetoprotein (AFP), insulin like growth factor-1 and IGF-binding protein-1 (IGFBP-1) (Muller et al, 1996;Bersinger and Odegard, 2004;Audibert et al, 2005;Venkatesha et al, 2006;Baumann et al, 2007;Spencer et al, 2008;Teixeira et al, 2008). Various studies have shown that the expression levels of these proteins increase or decrease according to the disorder and its degree in PE (Baumann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%